Phenotypes of painful TMD in discordant monozygotic twins according to a cognitive-behavioral-emotional model: a case-control study - Laís Valencise Magri; Melissa de Oliveira Melchior; Graziela Valle da Silva; Edilaine Cristina da Silva Gherardi-Donato; Christie Ramos Andrade Leite-Panissi (PLoS ONE, 2025)
Objectives This case-control study aimed to investigate variables based on a cognitive-behavioral-emotional model related to the development of painful temporomandibular disorders (TMD) in a sample of monozygotic twins discordant for the condition. Materials and Methods This case-control study investigated 20 monozygotic twins (10 pairs discordant for painful TMD), aged between 18 and 55. Participants were recruited through a comprehensive strategy following ethical approval, with inclusion criteria disseminated via social media, websites, local radio, messaging apps, and physical posters in public and healthcare spaces in Ribeirão Preto.The diagnosis of painful TMD was determined according to the Diagnostic Criteria for Temporomandibular Disorders - Brazilian Portuguese (DC/TMD). The cognitive-behavioral-emotional variables analyzed were a sociodemographic profile, pain sensitivity (pain threshold to pressure, allodynia, and hyperalgesia), oral behaviors, pain vigilance and awareness, pain catastrophizing, central sensitization, stress, anxiety, depression, alexithymia, mindfulness facets, sleep quality, pain control, pain intensity and interference, trigeminal and extra trigeminal pain areas. Bivariate logistic regression models were used to identify factors associated with TMD (p < 0.20), followed by multicollinearity analysis using Spearman’s correlation to exclude highly correlated variables. The final multiple logistic regression model included independent predictors to ensure robustness and accurate estimates, with statistical significance set at α = 0.05. Results While the adjusted model did not identify statistically significant associations, variables such as increased pain sensitivity in the masseter muscle (OR = 3.29, 95% CI: 0.17–62.8, p = 0.428), higher levels of pain catastrophizing (OR = 1.08, 95% CI: 0.64–1.8, p = 0.776), difficulty in externalizing feelings (OR = 1.61, 95% CI: 0.13–2.9, p = 0.539), and higher scores on the distraction facet of mindfulness (OR = 4.65, 95% CI: 0.39–55.7, p = 0.225) were included due to their clinical relevance and their significant associations in the bivariate analysis (p < 0.20). Conclusions Our study highlights the potential clinical relevance of cognitive-behavioral-emotional variables, such as increased pain sensitivity in the masseter muscle, higher levels of pain catastrophizing, difficulty in externalizing feelings, and higher scores on the distraction facet of mindfulness, in understanding painful TMD. While these variables did not show statistical significance in the adjusted model, their inclusion underscores the importance of exploring these factors in clinical practice. Further research is needed to validate these findings and clarify their role in the development and management of painful TMD. Clinical Relevance This study underscores the importance of cognitive-behavioral-emotional factors in the context of painful TMD, suggesting that variables like pain sensitivity and emotional regulation may be valuable for clinical assessment and management strategies. Despite the lack of statistically significant associations, these findings provide a foundation for future research to better understand and address the multidimensional nature of TMD in clinical practice.